Dietary non-nutritive factors on molecular targets of colorectal cancer: an update - Pandurangan, Ashok Kumar; Mohd Esa, Norhaizan (Asian Pacific Organization for Cancer Prevetion, 2013)
Colorectal cancer (CRC), a complex multi-step process involving progressive disruption of homeostatic mechanisms controlling intestinal epithelial proliferation/inflammation, differentiation, and programmed cell death, is the third most common malignant neoplasm worldwide. A number of promising targets such as inducible nitric acid (iNOS), cyclooxygenase (COX)-2, NF-E2-related factor 2 (Nrf2), Wnt/β-catenin, Notch and apoptotic signaling have been identified by researchers as useful targets to prevent or therapeutically inhibit colon cancer development. In this review article, we aimed to explore the current targets available to eliminate colon cancer with an update of dietary and non-nutritional compounds that could be of potential use for interaction with regulatory molecules to prevent CRC.